Operon-specific regulation of ribosomal protein synthesis in Escherichia coli. - Lindahl, L (1979)
We have cloned a DNA fragment harboring the genes for ribosomal proteins L2, L4, and L23 on a plasmid vector that contains a lac operator and promoter. The cloned ribosomal protein genes are now under the control of lacOP. Addition of a lac inducer to these cells results in a specific 5- to 10-fold increase in the synthesis of the proteins corresponding to the cloned genes. Within 10 min of this induction, the synthesis of ribosomal proteins S3, S19, L3, L16, L22, and L29 stops almost completely. The genes for all these proteins reside in the same chromosomal operon as L2, L4, and L23. We have seen no dramatic effect on the synthesis of any other ribosomal proteins. Thus, the induction of L2, L4, and L23 results in a specific and rapid decrease in the expression of all (or almost all) genes in their own transcription unit.